Diagnosis and management of metastatic neoplasms with unknown primary - Bochtler, Tilmann; Löffler, Harald; Krämer, Alwin (Seminars in diagnostic pathology, 2018)
In cancer of unknown primary (CUP), metastases are clinically and histologically confirmed, but the primary tumor site remains elusive after extensive work-up. CUPs make up for 2-3% of all epithelial malignancies. The two prevailing histologies are adenocarcinomas and undifferentiated carcinomas, whereas squamous cell carcinomas, neuroendocrine carcinomas and rare histologies account for the remaining 10%. The diagnostic work-up in CUP relies strongly on a detailed immunohistological (IHC) analysis in order to characterize the tumor type, nowadays aided by molecular techniques. Diagnostics also include a thorough clinical examination, a basic lab draw with the most relevant tumor markers, and cross sectional imaging. Additional PET-CT is recommended in cervical lymph nodes suggestive of head and neck cancer and in limited metastases potentially treatable in curative intent. As for treatment, it is paramount to identify patients who fall into one of the six well defined “favorable” subset categories, namely extragonadal germ cell tumors, adenocarcinoma with isolated unilateral axillary lymph nodes in female patients, squamous cell carcinoma with neck lymph nodes, squamous cell carcinoma with inguinal lymph nodes, serous papillary peritoneal carcinomatosis in females and blastic bone metastasis in males with elevated PSA. These subsets are distinct both regarding the required treatment and the comparably favorable prognosis. Within the remaining “unfavorable” group, patients of colon and renal cancer type should be identified based on IHC and clinical picture, since the prognosis of these patients seems to improve with the use of therapy tailored to the presumed primary as well. For the few patients with limited metastases it should be assessed whether they are candidates for surgery, radiotherapy or surgery followed by irradiation in curative intent. The remaining majority of patients are treated with empiric palliative chemotherapy, typically a platinum - paclitaxel combination, though the level of evidence for this therapy recommendation is low. Gemcitabine alone or in combination can be used as an alternative. Decoding of the molecular profiles in CUP offers the prospect of targeted therapy with novel agents. However, there appears to be no uniform molecular pattern for CUP, and the observed molecular diversity thus poses a challenge to respective clinical trials.